Untangling the co-effects of oriented nanotopography and sustained anticoagulation in a biomimetic intima on neovessel remodeling. (February 2020) - Wang, Zihao; Liu, Chungeng; Zhu, Di; Gu, Xiang; Xu, Yin; Qin, Qinghua; Dong, Nianguo; Zhang, Shengmin; Wang, Jianglin
Abstract: Constructing a small-diameter artificial blood vessel with biological functions and mechanical compliance comparable to native tissues is still a major challenge in vascular tissue engineering. To address the issues of severe thrombosis and unsatisfactory long-term patency in small-diameter vascular grafts, herein we designed a specifically biomimetic intima with an oriented nanotopographical structure and covalently immobilized anticoagulant molecules. The mixture of heparinized silk fibroin (SF-Hep) and polycaprolactone (PCL) was used to produce oriented inner layer and pure PCL was used to fabricate vertically porous outer layer by a two-step cross-electrospinning. Our findings showed that the immobilized heparin significantly influenced adherence and activation of platelets while the oriented nanotopography mainly manipulated the elongation and aligned growth of endothelial cells as well as hemodynamics of blood flow. More importantly, two factors of the oriented structure and anticoagulation presented the obviously synergistic effects on rapid endothelialization, long-term patency and remodeling of neovessel. Consequently, the current study successfully combined biochemical induction of heparin molecule and biophysical stimulation of oriented nanotopography to create an off-the-shelf small-diameter vascular graft with excellent antithrombosis in the early stage and long-term patency in the late stage.